Terapan Konsep Bangunan Tradisional Bali pada Objek Rancang-Bangun Karya Popo Danes - Aprimavista, Poela Art (Intra, 2013)
Cultural values as a nation identity increasingly more faded, even almost forgotten by the people of Indonesia. Technological advances and the development of the information society makes intensified focus his attention to a variety of technology products on the various objects of the culture of the nation.Popo Danes was one of the architects of Indonesia who have a love of culture, particularly the culture of Bali. Popo Danes many apply the love into many works of architecture. The problem is, in modern times it is today, its rare we see buildings that identifies the culture of Indonesia. This research aims to study the cultural values of applied nation Indonesia, especially Bali culture of the three objects of study draft Popo Danes are selected, using the concept of traditional building restrictions 5 Bali as a benchmarkÂ . The result analysis shows 2 conclusion. The first conclusion, the three objects of study having differences in the application of the concept of traditional Balinese building. And the second conclusion suggests that Popo Danes has always implemented the concept of the traditional Balinese buildings in every design, though in varying levels from one building to the other buildings.